THE PALESTINIAN PROBLEM IN THE MIDDLE EAST POLICY OF THE USSR / RUSSIA - T. V. Nosenko; V. A. Isaev; E. S. Melkumyan (Vestnik MGIMO-Universiteta)
The article reveals the stages in the formation of the USSR policy in the field of the Palestinian-Israeli conflict resolution, the features of the developed policy and practical conclusions that could be useful in advancing the current Middle East policy of the Russian Federation. Initially, the Soviet Union perceived the Palestinian theme primarily from the point of view of the problem of refugees. However, Moscow increasingly felt the need for reliable allies in the region. The movement for cooperation between the Palestine Liberation Organization and the USSR was bilateral: the PLO departed from revolutionary romanticism and began to follow a pragmatic line to expand contacts with opponents of Israel. Moscow began to consider the activities of the PLO as part of the national liberation movement, took a sharply anti-Israeli stance. Such a distortion led to a loss of freedom of maneuver in the region and to the announcement of deliberately non-constructive proposals for a Palestinian-Israeli settlement. Only since 1985 the USSR returned to a more flexible position, which sought to combine the interests of the Palestinian people and Israel. At the present stage, Russian diplomacy uses Soviet experience and connections, especially in the sphere of personal contacts. But Russia’s role in the Middle East conflict resolution has decreased due to subjective and objective reasons. Against the backdrop of the Arab Spring and the Civil War in Syria, Palestinian issues have become secondary in the agenda of Moscow, which, however, can lead to a new surge of violence and tension. Special relations with the Palestinian national liberation movement have always been an advantage of Soviet and then Russian diplomacy. The authors believe that this advantage should be used more actively to strengthen Russia’s positions in the region.